Surgical outcomes and risk factors for overall mortality in brain arteriovenous malformations patients: a retrospective analysis - Miron, Ioana; Pruna, Viorel M.; Visarion, Dan M.; Petrescu, George E. D.; Gorgan, Radu M. (Frontiers in Neurology, 2024)
Background Brain arteriovenous malformations (AVMs) are challenging vascular lesions. Extensive follow-up studies are necessary to refine the therapeutic algorithm, and to improve long-term survival in these patients. The aim of the study was to assess surgical outcomes, and to evaluate overall long-term mortality in patients treated for brain AVMs. Methods This retrospective single-center study included 191 patients with brain AVMs, admitted between 2012 and 2022. Clinical and angiographical particularities have been analyzed, to identify factors that might influence early outcome and overall long-term mortality. Results Out of 79 patients undergoing surgery, 51 had ruptured AVMs with total resection achieved in 68 cases (86.1%). Deep venous drainage was associated with incomplete resection. Female sex, admission modified Rankin Scale (mRS) > 2, and eloquent location were independent predictors of poor outcomes. Multiple venous drainage was associated with a higher risk of worsened early outcome. Eloquent brain region involvement, conservative treatment, increasing age, admission mRS > 2, and comorbidities significantly decrease survival in brain AVM patients. Patients treated with interventional treatments had significantly better survival than the conservatively managed ones, when adjusting for age and admission mRS. Conclusion The study identified female sex, poor neurologic status on admission and eloquence as independent prognostic factors for a negative outcome after surgery. Patients who received interventional treatment had significantly better survival than patients managed conservatively. We recommend employing tailored, proactive management strategies as they significantly enhance long-term survival in brain AVM patients.